2013
DOI: 10.3109/13685538.2013.768979
|View full text |Cite
|
Sign up to set email alerts
|

Circulating testosterone and estradiol, autonomic balance and baroreflex sensitivity in middle-aged and elderly men with heart failure

Abstract: The observed associations between reduced circulating androgens, oestrogens and lower HRV and depleted BRS, irrespectively of HF severity suggest the pathophysiological links between these two mechanisms. These results constitute the premises to investigate whether the pharmacological supplementation of depleted hormones would enable to restore the autonomic balance and improve the efficacy of reflex control within the cardiovascular system in men with systolic HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 53 publications
1
16
0
1
Order By: Relevance
“…These animals also demonstrated greater increases in microvascularization, thus generating greater nutrition and oxygenation of the organ, maintaining a balance of myocardium components and minimizing the morphofunctional changes associated with aging. These results are in accordance with the results showed by Rydlewska et al [24] and Florvaag et al [25], both papers show beneficial effects of testosterone treatment in cases of heart problems.…”
Section: Discussionsupporting
confidence: 93%
“…These animals also demonstrated greater increases in microvascularization, thus generating greater nutrition and oxygenation of the organ, maintaining a balance of myocardium components and minimizing the morphofunctional changes associated with aging. These results are in accordance with the results showed by Rydlewska et al [24] and Florvaag et al [25], both papers show beneficial effects of testosterone treatment in cases of heart problems.…”
Section: Discussionsupporting
confidence: 93%
“…Such studies have focused on men with known CVD. Rydlewska and colleagues noted that among men with mild systolic congestive heart failure, men with lower testosterone concentrations had decreases in parasympathetic tone as indicated by baroreflex sensitivity [29]. Similarly, Wranicz and colleagues noted than in 88 middle-aged men who had experienced a myocardial infarction, lower testosterone concentrations (<530 ng/dL) were associated with decreased (less favorable) heart rate variability [30].…”
Section: Discussionmentioning
confidence: 97%
“…This phenomenon seems to be more progressive in heart failure state leading inappropriate physical, cardiovascular, or psychological consequences. In a recent report, deficiencies in circulating testosterone were reported in 13% of heart failure patients that the reduced circulating testosterone was associated with lower heart rate variability and depleted baroreflex sensitivity [24]. In this line, it has been observed that low levels of growth hormone and testosterone have been associated with increased mortality and morbidity in patients with heart failure [25, 26].…”
Section: Discussionmentioning
confidence: 99%